Determinants of Profit Distribution Management - Tenny Badina (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to examine the effect of capital adequacy, effectiveness of third party funds, financing risk and the proportion of third party funds to profit distribution management in sharia banking in Indonesia period 2013-2016. The sample in this study is the Sharia Commercial Bank (BUS) which publishes quarterly financial reports in the period 2013-2016, which is listed in Bank Indonesia (BI) and the financial services authority (OJK). The data in this research is analyzed using multiple regression analysis method with IBM SPSS 23 software. The result of the research shows that the effectiveness variable of third party fund and the proportion of third party fund have significant effect to Profit distribution management. Meanwhile, the variable of capital adequacy and financing risk do not have influence to profit distribution management.